Prevalence of post-traumatic stress disorder among residents of Shanghai standardized training programs during the COVID-19 outbreak: a cross-sectional study - Huang, Ruiwen; Tang, Chao; Luo, Jianfeng; Li, Tingting; Wang, Li; Li, Chang; Cao, Lu; Wu, Shiyu (Frontiers in Public Health, 2023)
Background: The COVID-19 pandemic may have increased the prevalence of psychiatric disorders, such as anxiety, depressive disorders, and post-traumatic stress disorder (PTSD), among healthcare workers. Purpose: This study aims to investigate the prevalence of PTSD and its risk factors among residents in the standardized residency training programs (SRTPs) in Shanghai during the COVID-19 outbreak. Participants and Methods: An online cross-sectional survey was conducted between December 17, 2021, and January 7, 2022, among SRPT residents from 15 hospitals in Shanghai, China. Questionnaires comprising general information, medical-related traumatic event experiences, the PTSD Checklist (PCL-5), and the perceived social support scale (PSSS) were distributed to the participants using the online Questionnaire Star electronic system. Results: We included 835 valid responses for the analysis. In total, 654 residents (78.3%) had experienced at least one traumatic event, and 278 residents (33.3%) were found to have PTSD symptoms. The age 26-30 years old, female sex, and increased resident working hours were identified as the risk factors for PTSD (p < 0.05), and perceived social support had a significant negative association with PTSD (p < 0.05). Conclusion: During the COVID-19 pandemic, there was a high prevalence of PTSD among SRTPs residents in Shanghai. The age 26-30 years old, female sex, and increased resident working hours were identified as risk factors for PTSD, while perceived social support was identified as a protective factor against PTSD. The present findings can be applied in STRPs management and provide useful information for designing special interventions and protocols for SRTPs residents.